Studies on Growth, Competition Functions and Productivity of Baby Corn-cowpea Intercropping System under Various Crop Geometryand Nutrient Management - Karmakar, M.; Barik, A. K.; Ghorai, S. K. (International Journal of Bio-resource and Stress Management, 2017)
A field experiment was conducted during kharif season of 2012 and 2013 at agricultural research farm, Palli Siksha Bhavana (Institute of Agriculture), Visva-Bharati, Sriniketan, West Bengal to study the effect of crop geometry and nutrient management in baby corn and cowpea (fodder) intercropping system on growth, productivity and competition functions of intercropping systems. The experiment was laid out in randomized block design having twelve treatments with each treatment replicated thrice. Higher number of corns ha-1, baby corn yield and green fodder yield of baby corn and cowpea were found in sole crop of baby corn and cowpea. This was significantly higher than various intercropping systems. Total green fodder yield from different intercropping systems was higher than sole cowpea but lower than sole baby corn. The treatment having 3:1 row ratio of baby corn and cowpea 100% NPK of base crop+75% PK of intercrop exhibited significantly higher total fodder yield over sole crop of cowpea and lower than sole crop of baby corn. Baby corn+cowpea (fodder) at 2:2 row ratio with 100% NPK of base crop+75% PK of intercrop exhibited the highest LER, monetary advantage (MA) and Area-time equivalent ratio (ATER) followed by baby corn+cowpea (2:1) with 100% NPK of base crop+75% PK or 50% PK of intercrop. However, the highest Relative Value Total (RVT) and Aggressivity (A) was recorded in 3:1 row ratio of baby corn and cowpea with 100% NPK of base crop+75% PK of intercrop and with 100% NPK of base crop+25% PK of intercrop respectively. The Relative Crowding Co-efficient (RCC) was observed in 2:1 row ratio of ratio of baby corn and cowpea with 100% NPK of base crop+75% PK of intercrop.